Emerging Information Technologies and Delivering of Service Quality to Air Passengers: Case of South African Own-Registered Airlines - Nicholas O. Mantey; Vannie Naidoo (Journal of Economics and Behavioral Studies, 2018)
Increasingly services to airline passengers have evolved into the digital and technological realms. This study examined the extent to which South African own-registered airlines (SAORA) utilize emerging information technologies in delivering service quality to air passengers. The acronym â€œSAORAâ€ refers to Six South African own-registered airlines which was focus of this study. The research methodology adopted for this study was a descriptive approach focused on cross-sectional analysis. Using a quantitative research method and non-probability convenient sampling technique, primary data was collected from 684 passengers at O.R. Tambo International Airport in Johannesburg and King Shaka International Airport in Durban. The study revealed that by utilizing emerging technologies, SAORA stand to offer superior service quality to air passengers, thereby gaining competitive advantage, continuous patronage, loyalty and increased profitability.